Fostering cultural identity and self-expression through narrative poetry training at the Palangka Raya Youth Detention Center - Maida Norahmi; Susanty; Alifiah Nurachmana; Lesly Martha Cecylia Meka; Sulamit Syeba; Pujono; Olga Dona Retsi (University of Merdeka Malang, 2026)
The program aims to enhance the creative literacy of youth at The Juvenile Detention Center (Lembaga Pembinaan Khusus Anak/LPKA) through the learning and practice of narrative poetry writing while fostering awareness of local cultural values. As part of the educational and character development efforts within LPKA, this program guides participants to explore personal experiences, and cultural traditions as sources of inspiration for literary expression. To address this issue, narrative poetry is introduced as an effective medium to convey personal experiences, local legends, and cultural narratives in poetic form. The program was implemented at Youth Detention Center of Palangka Raya in collaboration with PKBM Darus Sa’adah Palangka Raya as a community learning partner. The program applied a participatory and contextual learning approach in which participants actively engaged in collaborative exploration of local cultural themes, and guided narrative poetry writing activities. A brief assessment was conducted through observation of participants’ involvement, review of the narrative poems produced, and short reflective discussions. The results demonstrate positive outcomes among participants. Observational data indicated that approximately 75 percent of participants actively engaged in discussions and writing activities and successfully organized narrative structures and incorporated local cultural elements into their poems reflecting aspects of local identity.